Angelina's Cinderella - Holabird, Katharine (Holabird, Katharine. Angelina Ballerina., 2024)
"Angelina and the other mouselings at Miss Lilly's Ballet School perform Cinderella on tour, battling homesickness and bad luck to ensure the show will go on"--